Gender Equality in Islamic Education: Promoting Democratic Values and Advancing SDGs 4 & 5 - Amal, Muhammad Ikhlasul; Luthfi, Sahensyah; Auliya, Kayyis Abiy (Universitas Muhammadiyah Surakarta, 2025)
This study aims to explore the development of gender discourse in Islamic education from 2015 to 2025 in the context of Sustainable Development Goals (SDGs) 4 and 5. Employing a bibliometric quantitative design, it analyzes 428 Scopus-indexed documents to identify publication trends, prolific authors, dominant disciplines, geographic distribution, influential works, and emerging research themes. The results show a significant rise in gender-related publications between 2019 and 2024, with a notable peak in 2024, suggesting increasing academic attention to gender equality in Islamic education. Indonesia emerged as the most prolific contributor, marking a shift in the epistemic center from the Middle East to Southeast Asia. A thematic analysis reveals an evolution from normative discourse to more critical and contextualized themes such as Islamic feminism, gender identity, and inclusive education. Uniquely, this study not only maps the literature but also examines mechanisms of discrimination and the moderating role of Islamic legal interpretation in achieving gender-based Islamic education, providing empirical and conceptual insights into how legal and cultural frameworks shape educational outcomes. The novelty lies in offering the first comprehensive knowledge mapping of gender discourse in Islamic education using bibliometric techniques, situating critique beyond content toward an ecosystem view of scholarly production. Within Islamic contexts, gender narratives are framed as fragmented despite underscoring holistic scholarly convergences and transformational restructuring opportunities—which enrich educational theory. On a practical level, the study contributes to policy formulation by advocating the integration of gender justice frameworks into Islamic curricula and calling for a paradigm shift from mere representation toward substantive structural transformation. It also raises the concern of “bibliometric activism”—surges in publication driven by institutional or geopolitical constructs rather than epistemologically rooted engagement—highlighting that while quantitative expansion of gender discourse in Islamic education is evident, qualitative depth remains emergent. Interdisciplinary engagement is thus essential for deepening theoretical development and strengthening its transformative potential.